Pengembangan Media Flashcard Kombinasi dalam Mata Pelajaran PPKn SMP Kelas VII - Astuti, Marshalita Debby Puji; Awaliyah, Siti; Suhartono, Edi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to produce a combination of flashcard media that was feasible, practical, attractive, and effective in the Pancasila and Civic Education subject in the Norms and Justice chapter. This study followed the development research stage of Borg and Gall. The subjects used were 34 students of class VII SMP Sunan Kalijogo Jabung. The study results showed that each validation test of media experts, materials experts, and learning experts obtained a percentage score of 100 percent. The results of the practicality test of combined flashcard media get a score percentage of 100 percent. The attractiveness of the combined flashcard media tested on a small group got a percentage of 95.2 percent and a large group of 94.7 percent. The results of the large group trial showed an increase from the pretest score of 33.3 percent to 66.6 percent in the posttest. Thus, based on all the trials that have been carried out, it was proven that the combined flashcard media in the Civics subject of SMP Class VII chapter of Norms and Justice could be categorized as very feasible, practical, attractive, and effective to use.